Problems for The Development of Students' Moral in Madrasah Tsanawiyah, Dolok Masihul, Serdang Bedagai - Zulfahri Zulfahri; Mulkan Hasibuan (PT ARRUS Intelektual Indonesia, 2022)
The problem in this study is moral education that must be owned and made a habit by a small child so that it becomes an adult, it can be understood that good and bad morals are closely related to moral development, therefore moral development needs to be considered so that the younger generation always has morals. Therefore, even though the students appear among them to have good morals, it is possible that they are far from actual morals. Methodology This research is a field research on the Problems of Student Moral Development in Madrasah Tsanawiyah, Dolok Masihul Serdang Bedagai District. Therefore, the data of this study were completely collected through field research. The results of the research The efforts made by the teacher in fostering the morals of students in this Mts madrasa include: Giving advice to students so that they maintain their good morals to themselves and their morals to others, motivating students to stay enthusiastic in learning, providing learning in accordance with Islamic law, provides sanctions or punishments for students who violate the rules that have been implemented at school.